Studies on endoscopic submucosal dissection in the past 15 years: A bibliometric analysis - Wu, Deqing; Jia, Mengyu; Zhou, Shu; Xu, Xiaorong; Wu, Meiqin (Frontiers in Public Health, 2022)
Background and aims Endoscopic submucosal dissection (ESD) is an advanced minimally invasive technique for en bloc resection of superficial gastrointestinal lesions, which is drawn an increasing attention from its emergence. This bibliometric analysis is to evaluate the origin, current hotspots, and research trends on ESD. Methods A total of 2,131 publications on ESD from 2006 to 2020 were obtained from the Web of Science Core Collection (WoSCC) database. Bibliometric visualization analyses of countries/regions, institutes, authors, journals, references and keywords were performed by CiteSpace V.5.8.R3. Results The quantity of publications on ESD increased significantly during the past 15 years. Japan occupied the leading position in terms of research power. Professor Yutaka Saito, together with the institute he belongs, the Endoscopy Division, National Cancer Center Hospital, Tokyo, Japan, were the most productive author and institute, respectively. Colorectal ESD led the main thematic concentrations in ESD research. The most prolific journal was Gastrointestinal Endoscopy. European ESD Guideline was the most frequently co-cited reference. Guideline, meta-analysis, endoscopic resection, poly-glycolic acid sheet, Barrett's esophagus, fibrin glue, risk and colorectal neoplasm will be the active research hotspots in the future. Conclusions These findings provide the trends and frontiers in the field of ESD, as well as valuable information for clinicians and scientists to discover the future perspectives with potential collaborators.